1965
DOI: 10.1084/jem.121.3.339
|View full text |Cite
|
Sign up to set email alerts
|

Antigenicity of Polypeptides (Poly Alpha Amino Acids)

Abstract: In continuation of studies to delineate some of the criteria for immunogenicity of synthetic random polymers of a-amino acids, we have investigated the contribution of the optical configuration of the amino acids. It was hoped that by studying the immunogenicity in several species of a variety of random terpolymers containing only D-a-amino acids or mixtures of D-and L-a-amino acids, some definite conclusions could be reached concerning the role of optical configuration in immunogenicity. Previously, we report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

1968
1968
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(23 citation statements)
references
References 24 publications
0
22
0
1
Order By: Relevance
“…This may be due to its repeating negative charge, its lack of L-amino acids and its unconventional peptide bonds [105]. Poor immunogenicity is consistent with the T-independent nature of bacterial polyanionic capsules [106,107].…”
Section: Capsule-based Vaccinesmentioning
confidence: 91%
See 1 more Smart Citation
“…This may be due to its repeating negative charge, its lack of L-amino acids and its unconventional peptide bonds [105]. Poor immunogenicity is consistent with the T-independent nature of bacterial polyanionic capsules [106,107].…”
Section: Capsule-based Vaccinesmentioning
confidence: 91%
“…Additionally, combining PA and FIS elicited better protection against fully virulent strains than either PA or FIS by itself. Glomski et al found that FIS could protect mice against a pXO1-negative spore challenge, and that this immunity was antibody independent [105]. Finally, an exosporium glycoprotein, BclA, has proven to be highly immunogenic [97] and might contribute to protection [42].…”
Section: Spore Antigensmentioning
confidence: 96%
“…Su poca capacidad inmunogénica se debe a su estructura química y a la carga negativa que posee, lo que determina que se comporte, prácti-camente, como un antígeno T-independiente (Chabot et al, 2004;Maurer et al, 1965;Schneerson et al, 2003;Wang et al, 2004).…”
Section: Vacunas Sobre La Base De Cápsulasunclassified
“…Long, linear γ-DPGA chains (~50 kDa) can be isolated from vegetative B. anthracis grown in vivo 38. For B. anthracis , the genes responsible for producing the γ-DPGA polymer,32 anchoring it to the peptidoglycan cell wall,35 and cleaving it into smaller dissociable fragments,33-36 augment its virulence perhaps through a variety of mechanisms, namely allowing the bacillus to resist complement33,39 and phagocytosis 36. Interestingly, during infection lower-molecular-weight capsular fragments (L-capsule) are released from the bacillus by the hydrolytic enzyme dep, or capD 33-36.…”
Section: Introductionmentioning
confidence: 99%